2019
DOI: 10.1007/s13353-019-00489-9
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency marker haplotypes in the genomic selection of dairy cattle

Abstract: The aim of this study was to predict the genomic breeding value (DGV) of production, selected conformation and reproductive traits, and somatic cell score of dairy cattle in Poland using high-frequency marker haplotypes. The dataset consisted of phenotypic, genotypic, and pedigree data of 1216 Polish Holstein-Friesian bulls. The genotypic data consisted of 54,000 single-nucleotide polymorphisms (SNPs). The data were divided into two subsets: a test dataset ( n = 1064) and a validation da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
(55 reference statements)
0
9
0
Order By: Relevance
“… Cuyabano et al (2015) also obtained gains in accuracy of up to 1.3% using pre-selected SNPs associated with the trait combined with the haplotypes as covariates in the models for production, fertility, and health traits. Mucha et al (2019) showed no differences in predictions with high-frequency haplotypes compared to SNPs when evaluating reproductive performance traits and somatic cell score in Polish dairy cattle. Additionally, Feitosa et al (2019) obtained nearly the same accuracy and bias for meat fatty acid (MFA) traits in Nellore cattle when fitting individual SNPs or haplotypes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… Cuyabano et al (2015) also obtained gains in accuracy of up to 1.3% using pre-selected SNPs associated with the trait combined with the haplotypes as covariates in the models for production, fertility, and health traits. Mucha et al (2019) showed no differences in predictions with high-frequency haplotypes compared to SNPs when evaluating reproductive performance traits and somatic cell score in Polish dairy cattle. Additionally, Feitosa et al (2019) obtained nearly the same accuracy and bias for meat fatty acid (MFA) traits in Nellore cattle when fitting individual SNPs or haplotypes.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies based on simulated data have shown that fitting haplotypes can substantially improve the performance of genomic predictions compared to individual SNP-based methods ( Calus et al, 2008 ; Villumsen et al, 2009 ). However, none or only small increases in the predictive ability of GEBVs have been observed in practice (e.g., Cuyabano et al, 2014 , 2015 ; Hess et al, 2017 ; Karimi et al, 2018 ; Mucha et al, 2019 ; Won et al, 2020 ). The large majority of the studies evaluating haplotype-based models were done in dairy cattle populations (real or simulated datasets), which usually have high LD levels between SNP markers and lower genetic diversity (Ne lower than 100; Makanjuola et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Haplotypes have been used widely in human genetics research (Curtis et al, 2001;Chapman et al, 2003;Curtis, 2007); in animal breeding studies, haplotypes have been used for the GP of breeding values with the use of high density SNP chips (Calus et al, 2008;Boichard et al, 2012;Cuyabano et al, 2014;Mucha et al, 2019). In this study, haplotype-based prediction models (G H BLUP and C H M) were applied to the whole genome-wide markers, and the result of this scenario was treated as a benchmark.…”
Section: Predictive Performance Of Haplotype-based Prediction Modelmentioning
confidence: 99%
“…To efficiently use the genome properties to define haploblocks and reduce the number of variables for the GP models, several researchers used only haplotypes with a high frequency in the population (Mucha et al, 2019) or based on LD threshold to define haploblocks (Cuyabano et al, 2015). For instance, Cuyabano et al (2014) used an average LD threshold (≥0.45) to construct haploblocks and found that prediction accuracies increased for the three traits compared with the commonly-used individual SNP.…”
Section: Predictive Performance Of Haplotype-based Prediction Modelmentioning
confidence: 99%
“…Health parameters, selection for organic production, reduced waste, and gas emission are also currently considered traits of interest [ 13 , 14 ]. Therefore, at present, it becomes necessary to add new parameters to genotype analyses to select animals with more accurate estimates of SNPs’ effects that directly or indirectly affect profitability [ 15 ]. Consequently, routine genotyping of primiparous cows and the incorporation of new indices such as inbreeding can significantly aid in making better management decisions in herds [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%